2009
DOI: 10.1021/jf803804k
|View full text |Cite
|
Sign up to set email alerts
|

PCR Marker-Based Evaluation of the Eating Quality of Japonica Rice (Oryza sativa L.)

Abstract: Evaluation of eating quality in early breeding generations of rice is critical to developing varieties with better palatability. This paper reports DNA markers associated with eating quality of temperate japonica rice and an evaluation method aided by multiple regression analysis. A total of 30 markers comprising STSs, SNPs, and SSRs were tested for their association with palatability using 22 temperate japonica varieties with different palatability values. Eating quality-related traits of the 22 varieties wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
89
1
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 18 publications
2
89
1
13
Order By: Relevance
“…A few studies have also identified QTLs for eating quality in doubled haploid (DH)lines or RILs derived from crosses between different japonica strains (Kobayashi and Tomita, 2008;Suh et al, 2006;Takeuchi et al, 2008;Tanaka et al, 2006;Wada et al, 2008). DNA markers closely linked to these QTLs have made it possible to more efficiently develop rice cultivars with a higher eating quality (Lestari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have also identified QTLs for eating quality in doubled haploid (DH)lines or RILs derived from crosses between different japonica strains (Kobayashi and Tomita, 2008;Suh et al, 2006;Takeuchi et al, 2008;Tanaka et al, 2006;Wada et al, 2008). DNA markers closely linked to these QTLs have made it possible to more efficiently develop rice cultivars with a higher eating quality (Lestari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…9) Lestari et al have used our primers and their original primers to develop an estimation formula for the results of the Mido-value of cooked rice grains. 10) Cooked rice is softened by the decomposition of the cell-wall, suggesting the important role of cell-walldegrading enzymes in the physical properties of the endosperm cell wall. Softening of the texture upon cooking by the addition of cellulase 11) and xylanase 12) has been reported.…”
mentioning
confidence: 99%
“…The physicochemical is influenced by starch content in the endosperm which is determined by amylose content (AC) and gel consistency (GC) [7]. Molecular markers for selection of high quality seed have been developed by many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Functional markers such as SSR, STS or SNP associated with genes related to the physicochemical properties of rice have been established [6,7,8]. Markers used previous studies are s3cl, sbe1, ss1, ssiia, gpa, gbss1, pul and ams [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation